2017
DOI: 10.1093/jpepsy/jsx142
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Transition From Pediatric to Adult Care: A Systematic Review

Abstract: Each chronic illness group experiences illness-specific challenges but certain barriers transcend chronic illness populations. Suggestions to overcome these barriers are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(171 citation statements)
references
References 81 publications
5
158
0
Order By: Relevance
“…Many in this study found the shift from the long‐standing relationships in the paediatric service to the impersonal consultations in the adult service difficult which echoes prior research (Fegran et al, ). A systematic review conducted in the United States concluded that “letting‐go of long‐standing relationships” was the most common barrier to transition (Gray, Schaefer, Resmini‐Rawlinson, & Wagoner, ). Given that AYAs value a trusting relationship with professionals, having an opportunity to get to know the adult team before transition can be particularly helpful for adjustment to the new team and adult environment.…”
Section: Discussionmentioning
confidence: 99%
“…Many in this study found the shift from the long‐standing relationships in the paediatric service to the impersonal consultations in the adult service difficult which echoes prior research (Fegran et al, ). A systematic review conducted in the United States concluded that “letting‐go of long‐standing relationships” was the most common barrier to transition (Gray, Schaefer, Resmini‐Rawlinson, & Wagoner, ). Given that AYAs value a trusting relationship with professionals, having an opportunity to get to know the adult team before transition can be particularly helpful for adjustment to the new team and adult environment.…”
Section: Discussionmentioning
confidence: 99%
“…A challenge in many chronic diseases with youth onset is the continuation of disease management through the transition from pediatric to adult care providers [20]. Indicators of disease management through this transition, as evidenced by glycemic control (HbA1c ≥ 75 mmol/mol [9.0%]), were examined in SEARCH in 182 young adults with type 2 diabetes who were initially receiving care through a pediatric provider, who reached age 18–25 while enrolled in SEARCH, and who had at least one follow-up in SEARCH after reaching age 18.…”
Section: Disease Managementmentioning
confidence: 99%
“…Central to an effective transition is the completion of comprehensive assessments and care plans, required to inform future treatments, interventions and support needs (Rochester‐Eyeguokan, Pincus, Patel, & Reitz, ). Nurses are in a key position to ensure collaboration and effective information sharing with other nurses in primary and acute care as well as specialist ID services (Gray, Schaefer, Resmini‐Rawlinson, & Wagoner, ).…”
Section: Relevance To Clinical Practicementioning
confidence: 99%